Development of Pop-Up Book Learning Media for Strengthening Pillars of Faith Comprehension in Junior High School Students - Aripuddin, Yuliani; Sukirman, Sukirman; Ratna, Ratna (Educational Journal of Learning Technology, 2025)
The lack of visual learning media causes students to have a shallow understanding of the pillars of faith material. This study aims to develop pop-up book-based learning media for Phase D students of grade IX. The study employed the 4D development model (Define, Design, Develop, Disseminate), utilizing data collection techniques that included interviews, questionnaires, tests, and documentation. The validation results showed a feasibility level of 75% (media), 95% (material), and 82.5% (language). The practicality of the media was assessed as high based on teacher responses (93.1%) and students (83.9%). The effectiveness of the media reached 87%. These findings indicate that pop-up book media can increase student involvement and understanding of the pillars of faith material.